Visualization of kidney fibrosis in diabetic nephropathy by long diffusion tensor imaging MRI with spin-echo sequence - Jun-Ya Kaimori (Nature Portfolio, 2017)
Abstract Renal fibrosis (RF) is an indicator for progression of chronic kidney disease (CKD). Although diabetic nephropathy (DN) is the leading cause of CKD and end-stage renal disease in Western populations, the ability of MRI to evaluate RF in DN patients has not been determined. As a first step to identify possible MRI methods for RF evaluation, we examined the use of diffusion tensor imaging (DTI) MRI to evaluate RF in a rat model of DN (SHR/NDmcr-cp(cp/cp): SHR/ND). The signal-to-noise ratio in DTI MRI was enhanced using a spin-echo sequence, and a special kidney attachment was developed for long-term stabilization. The changes in renal temperature and blood flow during measurement were minimal, suggesting the feasibility of this method. At 38 weeks of age, RF had aggressively accumulated in the outer stripe (OS) of the outer medulla. FA maps showed that this method was successful in visualizing and evaluating fibrosis in the OS of the SHR/ND rat kidney (r = 0.7697, P = 0.0126). Interestingly, in the FA color maps, the directions of water molecule diffusion in RF were random, but distinct from conventional water diffusion in brain neuron fibers. These findings indicate that DTI MRI may be able to evaluate RF in CKD by DN.